Ensino de conceitos sobre área e perímetro por meio da produção de histórias em quadrinhos - Moraes, Ketlin Nunes de (2020)
Comics have been entertaining, informing and educating their readers for over a century. Due to its own universal language, it can be used to influence the cultural formation of several generations. Given this potential, the present work foresees the use of Comics in Teaching Mathematics. With this perspective, this research presents a proposal for the use of HQ to address the curricular content of Geometry, in order to make possible the discussion of the main concepts, in different contexts. In particular, the content on perimeter and area of flat geometric figures is approached in order to relate the mathematical content and the comic strips to the problem situation about the geometric figures and their daily relations, taking as an element of investigation the municipal square of Planalto - PR. The work was developed in the form of a didactic Workshop for a multiseriate class of Elementary School II, which attends the Socioeducational Workshop offered by the Reference and Social Assistance Center of the Municipality against school shift. We detail the Workshop's proposal, report its development and describe the data collected and the results obtained with the application of this teaching strategy. In the data analysis process, we realized that the contributions of the didactic unit can be classified into four groups, proposed from qualitative indicators emerging from the observations on the students 'behavior during the scheduled activities and on the students' performance for the execution of the proposed tasks in each activity: 1) the motivation to participate in the activities; 2) the students' previous ideas on the topic addressed, 3) Mathematical concepts that involve activities and 4) Practical application of the acquired knowledge. In this sense, the results indicate that the proposed didactic unit, whose culminating point is the production of HQ, has elements that contribute to the individual and group motivation to carry out the activities and, when working in a way that the concepts are meaningful to the students under from a practical point of view, it adequately explores previous knowledge, allowing that knowledge to be extended and deepened.